'Singing has empowered, enchanted and enthralled me'-choirs for wellbeing?. (2nd February 2019) - Batt-Rawden, Kari; Andersen, Sarah
Summary: Singing in groups is a global phenomenon and there is a growing body of evidence that singing can affect health and wellbeing. This is the first gender-based study to explore how women's perceptions of their own health and wellbeing can be affected by singing in a choir; and also how choral singing may have an impact on social inclusion. Qualitative data was collected from nine choirs in two regions of Norway. The sample consisted of 19 ( n  = 19) women aged 21–75 (mean age, 51.3.) who had sung in choirs from 6 months to 20 years (mean, 6.2 years). The sample population included those who identified as 'healthy' and those experiencing health issues such as cancer, depression, anxiety or fatigue. Two focus groups and 16 semi-structured interviews were carried out and the data were analyzed using grounded theory. Findings were that choral singing can affect women's perceptions of their wellbeing in four distinct ways: (i) through the joy of singing, (ii) experiencing singing as essential for survival, (iii) group singing as a route to social connection, which enhanced a sense of identity and of belonging, and thereby increased self-confidence and self-esteem and (iv) through promoting social inclusion. In the context of these findings, choral singing can be understood as a 'salutogenic' activity, that is, one that supports health and wellbeing. This has implications for self-care practice, social prescribing programs and public health policy.